1972
DOI: 10.1007/bf02328117
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of nitrite and hydroxylamine byAspergillus flavus, peroxidase and catalase

Abstract: Hydroxylamine is metabolized by high concentrations of catalase, and about half of the hydroxylamine which disappears is recovered as nitrate. Horseradish peroxidase catalyzes the formation of nitrate in the presence of hydroxylamine, apparently by oxidizing a product of the spontaneous decomposition of the nitrogen compound. A.flavus extracts do not oxidize hydroxylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Then, nitrite was not oxidized, but it could be assimilated or denitrified by isolates. This is consistent with previous studies that showed that only few fungi are able to accumulate nitrate in organic medium (Schmidt 1959;Hora and Iyengar 1960;Marshall and Alexander 1961;Doxtader and Alexander 1965;Molina and Alexander 1972). However, nitrate tests used in this study detected only amounts greater than 5 mg N-NO3% (350 pmol NO3-/L), which were elevated compared with nitrite measurements but in the range of nitrate values observed for heterotrophic nitrifiers.…”
Section: Discussionsupporting
confidence: 92%
“…Then, nitrite was not oxidized, but it could be assimilated or denitrified by isolates. This is consistent with previous studies that showed that only few fungi are able to accumulate nitrate in organic medium (Schmidt 1959;Hora and Iyengar 1960;Marshall and Alexander 1961;Doxtader and Alexander 1965;Molina and Alexander 1972). However, nitrate tests used in this study detected only amounts greater than 5 mg N-NO3% (350 pmol NO3-/L), which were elevated compared with nitrite measurements but in the range of nitrate values observed for heterotrophic nitrifiers.…”
Section: Discussionsupporting
confidence: 92%
“…Cytochrome bd –type oxidases have been implicated with nitrosative stress resistance due to their high NO dissociation rate ( 51 ). Furthermore, katA and katE encode catalases that may be involved in NO 2 − detoxification to NO 3 − ( 52 , 53 ). Glutathione production and salvage are encoded by gshA , gshB , and ggt and are involved in numerous stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…On the A. faecalis genome, there are no genes that are homologous to the nitrite oxidase gene found in the autotrophic nitrite-oxidizing bacteria. Catalase-like nitrite oxidase (NiOx) has been reported in the heterotrophic nitrifying microorganisms Aspergillus flavus, Candida rugosa, and Bacillus badius 31 33 . The gene (AFA2_01914) encoding a catalase-like protein which shows sequence homology to the NiOx in B. badius 1–73 was found on the A. faecalis genome.…”
Section: Resultsmentioning
confidence: 99%